Developing the Concept of Sexual and Reproductive Health in Women with Type-1 Diabetes Mellitus: A Directed Content Analysis - Nasrin Azimi; Giti Ozgoli; Abbas Ebadi; Hamid Alavi majd; Assadollah Rajab; Zahra Kiani (Mashhad University of Medical Sciences, 2022)
Background & aim: Research has demonstrated the negative effects of type-1 diabetes mellitus (T1DM) on the female sexual health and reproductive function. The present study was conducted to develop the concept of sexual and reproductive health (SRH) in women with T1DM.Methods: This concept development was conducted by directed content analysis of relevant literature. A search was carried out for articles published from 2000 to 2019 in English databases including PubMed, Web of Science, Scopus, Embase and Persian databases including Magiran, SID, and IranDoc and search engine such as Google Scholar based on a search strategy developed for each database using Boolean operators. The initial matrix was designed based on the framework proposed by the United Nations Population Fund (UNFPA) and the World Health Organization (WHO) and information resources related to them for the concept of women's sexual and reproductive health (SRH). The selected articles were analyzed using directed content analysis with deductive approach proposed by Hsieh and Shannon. Results: The final codes were extracted from the review of 151 articles based on their conceptual differences and similarities, and categories were then defined and a matrix was developed. Four categories were extracted in this study for the concept of SRH in women with T1DM, including reproductive system, safe motherhood, sexual and gender-based violence, and sexual function, along with 20 subcategories.Conclusion: The findings can be utilized to develop specific tools for assessing SRH in women with T1DM as well as designing programs targeting SRH promotion in this vulnerable group.